COMPREHENSIVE REVIEW OF TRIAGE PROTOCOLS IN MASS CASUALTY INCIDENTS - Saleh Ahmad Saleh Al_ Saleh, Saleh Mana Hamad Alharthi , Abdullah Hussein Saleh Al Harkan, Ali Mohammed Abdulhadi Alzaqli, Khalid Ahmed Alajim, Abdulaziz Abdullah Moshabab Alyami, Ali Salem Mana Alsulayyim , Sara Ali Hussein Mohsen (Chelonian Research Foundation, 2022)
In the event of severe disasters, unimaginable numbers of casualties bombard health systems, creating a necessity for express and thoughtful verification of their condition and determining which needs immediate care. This paper considers the history, advantages, and shortcomings of programs and triage methods in MCIs. This paper's topic will be examined through a literature review, methodology, findings, and discussions. The aim will be to discover what triage systems are, what they consist of, and the factors influencing their implementation. Among the key findings were the importance of standardized triage protocols, training, practical communication, and coordination for emerging better from disasters. The article summarizes the results, suggesting potential enhancements to the current triage system and future strategies. Keywords: Triage, Mass Casualty Incidents, Triage Protocols, Emergency Response, Disaster Medicine